Endoluminální radiofrekvencní ablace krecových zil - Hnátek, L; Duben, J; Dudesek, B; Gatek, J (Rozhledy v chirurgii, 2007)
INTRODUCTION: Chronic venous insufficiency affects a considerable proportion of the population and, commonly, is not considered a disease, but a disease process presenting as a wide range of clinical findings. The commonest findings include stages C2 and C3 according to the CEAP classification. Recently, modern miniinvasive surgical methods have come forth. AIM: The aim is to present the authors intitial experience with endoluminal bipolar radiofrequency thermotherapy of varices (RFITT). MATERIAL, METHODOLOGY: 48 extremities operated in 35 subjects from January to June 2007. VSM (Vena saphaena magna) was operated in 47 cases and VSP (Vena saphaena parva) in a single case. Where terminal VSM valve insufficiency was detected, additional crossectomy was performed. In all subjects, the procedure was followed by mimiphlebectomy and foam sclerotherapy. RESULTS: Obliteration of the operated vein using RFITT immediately after the procedure rated 100%. Subsequent recanalization was performed in a single subject after Day 140. Complications included irritation of the saphenous nerve in three subjects, in one case following miniphlegectomy and in the other two cases following RFITT. In all the subjects, the clinical findings recovered spontaneously within 14 days. Duration of their hospitalization was 5-24 hours. CONCLUSION: RFITT is a safe and effective miniinvasive surgical technique in the varicose veins management. It can be considered another alternative to other miinvasive procedures, such as laser endoluminal photocoagulation or conventional procedures, including stripping.
Keywords: Female; mužské pohlaví; lidé; Catheter Ablation; Varicose Veins; varixy; Adult; Aged; katetrizační ablace; Male; Humans; dospělí; ženské pohlaví; Middle Aged; lidé středního věku; senioři